2019
DOI: 10.1097/md.0000000000015425
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the opioid crisis in the US healthcare system

Abstract: Introduction: The administration of opioids has been used for centuries as a viable option for pain management. When administered at appropriate doses, opioids prove effective not only at eliminating pain but further preventing its recurrence in long-term recovery scenarios. Physicians have complied with the appropriate management of acute and chronic pain; however, this short or long-term opioid exposure provides opportunities for long-term opioid misuse and abuse, leading to addiction of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
119
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 71 publications
0
119
0
6
Order By: Relevance
“…[24] These findings may be of use in developing targeted efforts to prevent fatal opioid overdoses. [25,26,27] Compared to Hispanics, Whites had the highest HRs for opioid overdose death. This disparity, affecting the largest U.S. racial group, [5] has been attributed to socioeconomic despair [4] and limited opportunity in distressed U.S. communities [28] Other explanations U.S. policy priorities for health care, healthy behaviors, and the physical and social environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] These findings may be of use in developing targeted efforts to prevent fatal opioid overdoses. [25,26,27] Compared to Hispanics, Whites had the highest HRs for opioid overdose death. This disparity, affecting the largest U.S. racial group, [5] has been attributed to socioeconomic despair [4] and limited opportunity in distressed U.S. communities [28] Other explanations U.S. policy priorities for health care, healthy behaviors, and the physical and social environment.…”
Section: Discussionmentioning
confidence: 99%
“…If SES partially mediated the effect of race in the final model, then interventions that impact SES, such as improving education, may have among their many advantages, the ability of help decrease opioid overdoses and associated racial disparities. [25][26][27][28] Furthermore, although the opioid epidemic has been most acute in some areas with low percentage Black populations, [7] (e.g., Appalachia, New England, the Midwest, and Mountain states), the recent shift toward a more urban centered opioid overdose epidemic [8] and high opioid overdose fatality rates in other areas with sizeable Black populations (e.g., Southeastern U.S.) could place Blacks at risk moving forward. People who were disabled had almost three times higher risk of death from opioid overdose than those without a disability, likely reflecting use of opioid analgesics to treat chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in the United States, an epidemic of misuse of opioids is causing 33,000 deaths per year, through both prescribed and illegal use of opioids. 4,5 In a recent review, Stoicea et al concluded that with approximately 100 million people suffering from both chronic and acute pain in the United States in 2016, opioids would continue to remain highly prescribed medicines across the US. 5 More than two thirds of overdose episodes in 2016 were opioid-related.…”
mentioning
confidence: 99%
“…4,5 In a recent review, Stoicea et al concluded that with approximately 100 million people suffering from both chronic and acute pain in the United States in 2016, opioids would continue to remain highly prescribed medicines across the US. 5 More than two thirds of overdose episodes in 2016 were opioid-related. 5 Nonetheless, this is not the first crisis relating to use of opioids over the course of the history of humanity.…”
mentioning
confidence: 99%
See 1 more Smart Citation